A Landscape-Scale Adjoining Conservation (LAC) Approach for Efficient Habitat Expansion: The Case of Changbai Mountain, Northeast China - Jianwei Bai (Sustainability, 2018)
The biodiversity crisis and ecosystem degradation caused by habitat destruction and human activities can be reduced by organizing protected areas. However, many protected areas currently take the form of “green islands,” which has led to serious habitat isolation in many places. We thus introduce herein a landscape-scale adjoining conservation (LAC) approach for the protection and restoration of ecosystems across the boundaries between protected areas and surrounding non-protected areas. The strategy of the LAC approach is to effectively expand conservation areas by connecting isolated areas of important ecosystems or habitats outside of protected areas. The methodology of the LAC approach involves integrated analyses that consider both habitat quality and landscape patterns. Forest-habitat quality is characterized by species composition and stand structure, and habitat connectivity is quantified by the max patch area of habitat and total habitat area. The focal statistic is useful for examining habitat clumps that result from landscape fragmentation. As a case study, we apply the LAC approach to adjoining restoration of broadleaf Korean pine mixed forest on the Changbai Mountain in northeastern China. We developed a metric called the Restoration Efficiency of Landscape Expansion (RELE) to evaluate the LAC approach. The results indicate that a minimal restoration effort can produce significant effects in terms of the expansion of contiguous habitat, as quantified by RELE.